2016
DOI: 10.1590/0103-8478cr20151414
|View full text |Cite
|
Sign up to set email alerts
|

Megaesophagus in sheep and goats

Abstract: Megaesophagus is a rare disease in ruminants characterized by regurgitation of rumen contents. In this paper it was described cases of megaesophagus in two sheep

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…This case report expands the list of differential diagnoses for abnormal regurgitation and provides another specific cause of obstructive gastrointestinal disease in sheep. To the authors' knowledge, similar cases in sheep have only twice been reported in the literature (Cockcroft 1993, Braun and others 2014) while the identification of acquired megaoesophagus in true ruminants appears sporadically (Morgan 1965, Kasari 1984, Braun and others 1990, Jalilzadeh‐Amin and Hashemiasl 2015, Nascimento and others 2016).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This case report expands the list of differential diagnoses for abnormal regurgitation and provides another specific cause of obstructive gastrointestinal disease in sheep. To the authors' knowledge, similar cases in sheep have only twice been reported in the literature (Cockcroft 1993, Braun and others 2014) while the identification of acquired megaoesophagus in true ruminants appears sporadically (Morgan 1965, Kasari 1984, Braun and others 1990, Jalilzadeh‐Amin and Hashemiasl 2015, Nascimento and others 2016).…”
Section: Discussionmentioning
confidence: 92%
“…To the authors' knowledge, similar cases in sheep have only twice been reported in the literature (Cockcroft 1993, Braun and others 2014) while the identification of acquired megaoesophagus in true ruminants appears sporadically (Morgan 1965, Kasari 1984, Braun and others 1990, Jalilzadeh-Amin and Hashemiasl 2015, Nascimento and others 2016). …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…26 In ruminants, muscular dystrophy secondary to vitamin E deficiency has been observed. 11 Although the full medical history of this rabbit is unknown, as it was a rescued pet, the animal was fed a strict pelleted diet. Indeed, despite pelleted feeds being a non-optimal diet as hay and vegetables should be offered, they are supplemented in multiple minerals and vitamins including vitamin E. 27 Moreover, as whole pellets and not the muesli type was offered, the rabbit could not have induced a deficiency by selecting only the most savoury parts.…”
Section: Discussionmentioning
confidence: 99%
“…In goats and sheep with megaoesophagus, similar muscular necrosis and loss of striation have been described based on histopathological analysis. 11 In these cases, it was hypothesised that ingestion of an undiscovered toxic plant could have resulted in these lesions. In our case, toxicities and infections were considered less likely, as the animal remained alone in a cage indoors and had no free roaming.…”
Section: Discussionmentioning
confidence: 99%